Water and Nutrient Management in Natural and Constructed Wetlands - Vymazal, Jan.; SpringerLink (Online service) (Dordrecht : Springer Netherlands : Imprint: Springer, 2011)
Wetlands provide a wide variety of ecosystem services within the landscape and their importance is commonly accepted. Among the most important are regulating services, i.e., benefits obtained from the regulation of ecosystem processes. For example, wetlands contribute to climate regulation. Land cover can affect local temperature and precipitation, wetland ecosystems may affect greenhouse gas sequestration and emissions, or affect the timing and magnitude of runoff and flooding, for example. Wetlands also improve water quality through mechanical, physical, physico-chemical, biological and biochemical processes. These abilities are also used in constructed wetlands but within a more controlled environment. In addition, wetlands provide the supporting services necessary for the production of all other ecosystem services such as soil formation and retention, nutrient cycling, primary production or water cycling. In short, wetlands are clearly among the most valuable ecosystems on Earth. In order to provide these services, wetlands need to be properly evaluated, protected and maintained. This book provides results of the latest research in wetland science around the world. Chapters deal with such topics as the use of constructed wetlands for treatment of various types of wastewater, use of constructed wetlands in agroforestry, wetland hydrology and evapotranspiration, the effect of wetlands on landscape temperature, and chemical properties of wetland soils. This book will be of interest for classes in environmental science, researchers, ecologists, landscape planners and regulators.
From the Table of Contents: Application of Constructed Wetlands in Recycling, Agriculture and Agroforestry:Water Management for Changing Flow Regimes -- Properties of Biosolids from Sludge Treatment Wetlands for Land Application -- Process Based Models for Subsurface Flow Constructed Wetlands -- Application of Vertical Flow Constructed Wetlands for Highly Contaminated Wastewater Treatment: Preliminary Results -- Comparison of Performance, Ageing and Eco Balance Data from Four Types of Constructed Wetlands Treating Raw Sewage ... Factors Affecting Metal Mobilisation During Oxidation of Sulphidic, Sandy Wetland Substrates -- The Presence of Mycorrhiza in Different Habitats of an Intermittent Aquatic Ecosystem -- Comparison of Reflected Solar Radiation, Air Temperature and Relative Air Humidity in Different Ecosystems: from Fishponds and Wet Meadows to Concrete Surface.
Keywords: Environmental sciences; Applied Ecology; Endangered ecosystems; Landscape ecology; Plant Ecology; Environmental pollution; Environment; Waste Water Technology / Water Pollution Control / Water Management / Aquatic Pollution; Applied Ecology; Landscape Ecology; Plant Ecology; Ecosystems